Imagem e percepção de valor em esquadrias de alumínio e PVC - Dalberto, Mikael (My University, 2014)
The Brazilian civil construction market lives nowadays its best moment, influenced by the program of accelerated growth represented by investments in infrastructure and mainly the easy access to credit for home ownership. In the city of Caxias do Sul, the civil construction, which uses frames, presented a growth of 40% in the period from 2009 to 2011. Despite the growing expansion of civil construction, the segment of aluminum frames and PVC still needs the attention of researchers as regards its image and perception of value. In this sense, this study sought to identify the attributes forming the images of aluminum frames and PVC, the way they are configured in size and levels of the image, and how these dimensions impact the perception of value from the perspective of consumers in the city of Caxias do Sul - RS. The research methodology used is characterized as exploratory research, with qualitative and quantitative approaches, based on the adaptation of the Image Configuration Method (ICM), research instrument tested and validated to identify the images of organizations and products. The results demonstrated a solid image of the aluminum frames, being composed by functional, emotional, cognitive and symbolic dimensions, with predominance of the functional dimension. Moreover, it is observed that the cognitive and functional dimensions have a more significant impact on the perceived value of the aluminum frames. For the frames of PVC was observed that this is a new product on the market and particularly applicable to high standards in real estate. Its image is composed of functional, emotional, cognitive and symbolic dimensions, with predominance of the functional dimension. However there was the presence of the ‘bad finishing ‘negative attribute in the central image. In this sense, the study of the image of frames helps communication and marketing professionals in the direction of actions aimed at strengthening the image of the products, as well as the direction to reverse the negative attributes that may impact the perception of value or purchase intention toward these products. [resumo fornecido pelo autor]
O mercado da construção civil brasileira vive atualmente seu melhor momento, influenciado pelo programa de aceleração do crescimento representado por investimentos em infraestrutura e principalmente pelo fácil acesso ao crédito para aquisição da casa própria. Na cidade de Caxias do Sul a construção civil, a qual utiliza esquadrias, apresentou crescimento de 40% no período de 2009 à 2011 . Apesar da crescente expansão da construção civil, o segmento de esquadrias de alumínio e PVC ainda carece da atenção dos pesquisadores no que diz respeito a sua imagem e percepção de valor. Neste sentido, o presente trabalho buscou identificar os atributos formadores das imagens das esquadrias de alumínio e PVC, como eles se configuram em dimensões e níveis da imagem, e como estas dimensões impactam na percepção de valor sob a ótica dos consumidores da cidade de Caxias do Sul - RS. A metodologia de pesquisa utilizada caracteriza-se como pesquisa exploratória, com abordagens qualitativa e quantitativa, embasada na adaptação do Método de Configuração de Imagem (MCI), instrumento de pesquisa testado e validado na identificação das imagens de organizações e produtos. Os resultados encontrados demonstram a imagem sólida das esquadrias de alumínio, sendo composta pelas dimensões funcional, emocional, cognitiva e simbólica, tendo predominância da dimensão funcional. Além disso, observa-se o significativo impacto da imagem das esquadrias de alumínio sobre a percepção de valor. Para às esquadrias de PVC observou-se que trata-se de um produto novo no mercado e aplicável principalmente em imóveis de alto padrão. Sua imagem é composta pelas dimensões funcional, emocional, cognitiva e simbólica, tendo predominância da dimensão funcional. Entretanto verificou-se a presença do atributo negativo acabamento ruim na imagem central. Nesse sentido, o estudo da imagem de esquadrias auxilia os profissionais de comunicação e marketing no direcionamento das ações que visem o fortalecimento da imagem dos produtos, bem como o direcionamento para a reversão dos atributos negativos. [resumo fornecido pelo autor]
Keywords: Marketing; Consumidores; Comportamento do consumidor; Construção civil - Caxias do Sul (RS); Consumer behavior; Image configuration; Image dimensions